Retrospective study for correlation analysis of nutritional status with osteoporosis, sarcopenia and cognitive impairment in elderly patients with coronary heart disease - Xu, Xiao; Li, Daohong; Zhang, Shan (Frontiers in Cardiovascular Medicine, 2024)
Coronary heart disease (CHD) is an abbreviation of coronary atherosclerotic heart disease, which remains challenging for diagnosis and treatment. Current study aims to explore the correlation between geriatric nutritional risk index (GNRI) and osteoporosis, sarcopenia, cognitive dysfunction in elderly patients with CHD, and to analyze the clinical diagnostic value of GNRI in the above complications. A total of 92 elderly patients with CHD treated in Suzhou Ninth People's Hospital from January 2020 to October 2023 were retrospectively collected as the experimental group, and 68 non-CHD subjects matched for sex and age in the same period of physical examination were randomly selected as the control group. Osteoporosis, sarcopenia and cognitive dysfunction were analyzed in all patients, and the correlation between GNRI and these indices in different populations was analyzed by Spearman's rank correlation. The diagnostic efficacy of GNRI in osteoporosis, sarcopenia, and cognitive impairment was analyzed by ROC curves. There was no significant difference in age, sex distribution, body mass index (BMI) and serum biological indexes between the elderly patients with CHD and the control group (all P > 0.05). Correlation analysis showed that GNRI level was positively correlated with bone mineral content (BMC), bone mineral density (BMD) T value and osteocalcin (OCN) (All r > 0, P < 0.05). In addition, GNRI levels were positively correlated with skeletal muscle mass (ASMI), grip strength and calf circumference (CC) (All r > 0, P < 0.05). However, there was no significant correlation between GNRI levels and cognitive dysfunction-related indicators (P > 0.05). In the elderly and elderly with CHD, the diagnostic AUC of GNRI was 0.875 and 0.862 in osteoporosis, and 0.912 and 0.932 in sarcopenia, respectively. The level of GNRI is significantly correlated with osteoporosis and sarcopenia. GNRI level, as an auxiliary diagnostic tool in elderly patients with CHD, exerts important clinical significance for early detection of the risk of complications, such as osteoporosis and sarcopenia.